From Mustahiq to Contributors: Productive Zakat and Sustainable Community Empowerment in Kampung Zakat Gredek - Vina Fithriana Wibisono; Choirunnisa Adyanti; Nurul Adilah Hasbullah (Mabny: Journal of Sharia Management and Business, 2026)
Purpose  This study examines how productive zakat contributes to sustainable community empowerment through the Kampung Zakat Program in Gredek Village, Gresik Regency. Specifically, it explores how the program facilitates the transformation of mustahiq from passive recipients of assistance into active contributors to community welfare and analyzes this transformation through the Maqashid Sharia framework. Methodology This study employed a qualitative descriptive approach. Data were collected through interviews, observations, and documentation involving administrators of the Village Zakat Collection Unit (UPZ), village officials, and beneficiaries of productive zakat programs. The data were analyzed using descriptive qualitative techniques and interpreted through the dimensions of hifz al-din (preservation of religion) and hifz al-mal (preservation of wealth). Findings  The findings reveal four major contributions of the Kampung Zakat Program. First, productive zakat improved benefit income and business sustainability through business capital assistance, productive facilities, and entrepreneurship mentoring. Second, the program implemented an integrated empowerment model that combined economic assistance, social protection, healthcare support, and religious development activities. Third, productive zakat generated a village economic multiplier effect by involving local entrepreneurs in the provision of business facilities, thereby strengthening local economic circulation. Fourth, and most importantly, the program facilitated the transformation of mustahiq from passive recipients into active contributors through participation in philanthropic initiatives, community activities, and religious programs. From the Maqashid Sharia perspective, these outcomes reflect the realization of both hifz al-din and hifz al-mal through the promotion of religious awareness, charitable behavior, sustainable wealth development, and community welfare. Implications The findings suggest that productive zakat programs should move beyond financial assistance by integrating entrepreneurship development, continuous mentoring, social participation, and religious empowerment to achieve sustainable community development outcomes. Originality This study contributes to the literature on productive zakat by demonstrating how zakat-based empowerment can generate local economic multiplier effects and facilitate the transformation of mustahiq into active contributors within a Maqashid Sharia framework. The study further proposes an integrated empowerment model that combines economic, social, health, and religious dimensions at the village level.